Características epidemiológicas y nivel de gravedad de la colecistitis aguda en pacientes de emergencia Hospital Regional de Loreto 2022 - Flores Flores, Dennys David (2025)
The objective of the study was to determine the relationship that exists between the epidemiological characteristics and the level of severity of acute cholecystitis in emergency patients Hospital Regional de Loreto Iquitos 2022, the method was quantitative, non-experimental, descriptive, correlational cross-sectional design. The population and sample were 130 medical records of patients with acute cholecystitis. The technique was the documentary review and the instruments, Epidemiological data sheet of patients with acute cholecystitis and the record sheet for identifying the level of severity of acute cholecystitis. For data processing and analysis, the statistical package SPSS version 24.0 and the non-parametric inferential test of free distribution Chi Square (X2) with a significance level of α 0.05 were used. The results were: 43.1% were between 18 and 35 years old, 73.8% were female, 42.3% were cohabitants, 37.7% did not have any children, 62.3% had degree of secondary education, 50.7% had independent occupation and 37.7% presented hypertension, 72.3% presented the disease recently and 70.7% came from urban areas. Regarding the level of severity of acute cholecystitis, 71.5% had a mild level of severity and the remaining 28.5% had a moderate level. In conclusion, an association was found between the level of severity of acute cholecystitis and the epidemiological characteristics of the patient, age p=0.035, sex p=0.012 and comorbidity p=0.001. Likewise, no association was found with the epidemiological characteristics of the patient, duration of illness p=0.662, marital status p=0.680, number of children p=0.263, level of education p=0.449, occupation p=0.893, and origin p =0.190.